Involvement of an expert and conduction of an expert examination within criminal proceedings in the environmental sphere - L. Yu. Misiura (Law and Safety)
The types of examinations which can be carried out within criminal proceedings in the environmental sphere have been determined. The procedure for involving an expert and conducting an expert examination within criminal proceedings in the environmental sphere has been revealed. The problematic aspects of an investigator, prosecutor’s activity at the specified stage of pre-trial investigation of criminal offenses against the environment have been highlighted.